3(f-10)=-21

Simple and best practice solution for 3(f-10)=-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(f-10)=-21 equation:


Simplifying
3(f + -10) = -21

Reorder the terms:
3(-10 + f) = -21
(-10 * 3 + f * 3) = -21
(-30 + 3f) = -21

Solving
-30 + 3f = -21

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 3f = -21 + 30

Combine like terms: -30 + 30 = 0
0 + 3f = -21 + 30
3f = -21 + 30

Combine like terms: -21 + 30 = 9
3f = 9

Divide each side by '3'.
f = 3

Simplifying
f = 3

See similar equations:

| -10(s+2)=43 | | 3x^3=4x+11 | | 2(4s+10)=116 | | 5(2l+7)=135 | | 3(a-10)=3 | | 4cosx+2sinx=3 | | (q-6)*3=9 | | (q-6)*4=9 | | 6(3s+8)=156 | | 5(a-3)=65 | | 8x^2-2xy*-3y^2=0 | | 3+91x=39x+11 | | 2x^2=3x+12 | | 3a^2+a-10=0 | | 24-6x=12-8x | | (A-3)(3a-1)= | | -3.6r-4.5r=-6.48 | | 5.5+2.2n-4.789n=-3.3026 | | -3.5x+3.3x=0.86 | | 2(3x-4)+3(2x+2)=142 | | (x+5)(y-3)=0 | | 4x+11=-43-5x | | -4.3r-2.2r=13 | | (2z+6)(z-2)= | | m+2.6+0.26=3.76 | | xy+5y-3x=15 | | 4.79n+3.9n=-13.035 | | X-0.80X=5159 | | 20x+55y=92.65 | | 5x+x-10=20-6x | | x(2)+8=24 | | 0.837x-2.1+3.6x=17.498229 |

Equations solver categories